A meta-analysis and systematic review of the comorbidity between irritable bowel syndrome and bipolar disorder. Issue 33 (August 2016) - Tseng, Ping-Tao; Zeng, Bing-Syuan; Chen, Yen-Wen; Wu, Ming-Kung; Wu, Ching-Kuan; Lin, Pao-Yen
Abstract : Abstract: Irritable bowel syndrome (IBS) and bipolar disorder (BD) are 2 distinct diseases but may share a similar pathophysiology. However, the comorbidity rate of these 2 diseases is unclear. Also, the current practice guidelines suggest prescribing antidepressants to IBS patients. However, this practice may increase the risk of phase-shift to manic episodes in IBS patients comorbid with BD. This study aimed to determine the relationship between IBS and BD through a meta-analysis. Electronic research through PubMed, Medline, ScienceDirect online, ClinicalTrials.gov, and additional resources. The inclusion criteria were studies investigating the prevalence rate of BD in subjects with IBS and control subjects; and articles on clinical trials on humans. Data from included studies were pooled by a random effects model, and possible confounding variables were examined by meta-regression and subgroup analysis. The current study consists of a total of 177, 117 IBS patients and 192, 092 control subjects extracted from 6 included studies. The prevalence rate of BD was significantly higher in the IBS patients than in the controls (odds ratio = 2.48, 95% confidence interval: 2.35–2.61, P < 0.001). However, the significance persists only in studies from database research, but not from primary studies. In addition, there was no significant association between the prevalence rate of BD in IBS and several clinical variables, including age, female proportion, prevalence of comorbid diabetes, or hypertension. The total number of included studies is small. Moreover, apparently different results from database research and primary research limit the generalization of our findings to a broad population. Also, we could only perform meta-regression on limited clinical variables. Our results support a significantly higher prevalence rate of BD in IBS patients than in controls. Clinicians should be cautious about the risk of phase-shift to manic episodes when prescribing antidepressants in IBS patients under current practice guidelines. Abstract : Supplemental Digital Content is available in the text